Metallothionein isoforms as double agents – Their roles in carcinogenesis, cancer progression and chemoresistance. (September 2020) - Merlos Rodrigo, Miguel Angel; Jimenez Jimemez, Ana Maria; Haddad, Yazan; Bodoor, Khaldon; Adam, Pavlina; Krizkova, Sona; Heger, Zbynek; Adam, Vojtech
Abstract: Metallothioneins (MTs) are small cysteine-rich intracellular proteins with four major isoforms identified in mammals, designated MT-1 through MT-4. The best known biological functions of MTs are their ability to bind and sequester metal ions as well as their active role in redox homeostasis. Despite these protective roles, numerous studies have demonstrated that changes in MT expression could be associated with the process of carcinogenesis and participation in cell differentiation, proliferation, migration, and angiogenesis. Hence, MTs have the role of double agents, i.e., working with and against cancer. In view of their rich biochemical properties, it is not surprising that MTs participate in the emergence of chemoresistance in tumor cells. Many studies have demonstrated that MT overexpression is involved in the acquisition of resistance to anticancer drugs including cisplatin, anthracyclines, tyrosine kinase inhibitors and mitomycin. The evidence is gradually increasing for a cellular switch in MT functions, showing that they indeed have two faces: protector and saboteur. Initially, MTs display anti-oncogenic and protective roles; however, once the oncogenic process was launched, MTs are utilized by cancer cells for progression, survival, and contribution to chemoresistance. The duality of MTs can serve as a potential prognostic/diagnostic biomarker and can therefore pave the way towards the development of new cancer treatment strategies. Herein, we review and discuss MTs as tumor disease markers and describe their role in chemoresistance to distinct anticancer drugs.